2008
DOI: 10.1029/2008jd010639
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation on mineral dust particles: Onset conditions, nucleation rates and contact angles

Abstract: [1] An optical microscope coupled to a flow cell was used to investigate the onset conditions for ice nucleation on five atmospherically relevant minerals at temperatures ranging from 233 to 246 K. Here we define the onset conditions as the humidity and temperature at which the first ice nucleation event was observed. Kaolinite and muscovite were found to be efficient ice nuclei in the deposition mode, requiring relative humidities with respect to ice (RH i ) below 112% in order to initiate ice crystal formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
161
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(185 citation statements)
references
References 70 publications
23
161
1
Order By: Relevance
“…Experiments were carried out with a slightly modified apparatus to that used for ice nucleation experiments of organic materials (Parsons et al, 2004), mineral dust (Eastwood et al, 2008), and soot (Dymarska et al, 2006). The current method allows for observations of the freezing of spore-containing water droplets.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were carried out with a slightly modified apparatus to that used for ice nucleation experiments of organic materials (Parsons et al, 2004), mineral dust (Eastwood et al, 2008), and soot (Dymarska et al, 2006). The current method allows for observations of the freezing of spore-containing water droplets.…”
Section: Methodsmentioning
confidence: 99%
“…We extend this database by investigating the effects of relative humidity on the uptake of N 2 O 5 to illite, one of the most abundant clay minerals in dust particles (Chester, 1990;Claquin et al, 1999;Nickovic et al, 2012) and one of the most efficient ice nuclei in the troposphere (Eastwood et al, 2008;Zimmermann et al, 2008 4 (where M is a monovalent interlamellar cation), is a non-expansive clay mineral characterized by aluminosilicate layers containing one octahedral alumina sheet sandwiched by two tetrahedral silica sheets (Hatch et al, 2012). At room temperature one monolayer of surface-adsorbed water is formed at ∼ 15 % RH (Hatch et al, 2012), and the amount of adsorbed water increases to 0.15-0.2 g water per gram illite (corresponding to ∼ 60-80 formal monolayers of water) at ∼ 70 % RH (Schuttlefield et al, 2007;Hatch et al, 2012).…”
Section: J Tang Et Al: Heterogeneous Reaction Of N 2 O 5 With Ilmentioning
confidence: 99%
“…Homogeneous nucleation is significant at temperatures below −38 • C. At higher temperatures the formation of ice in clouds is triggered by heterogeneous nucleation which is divided into four sub-processes: Immersion, condensation, contact and deposition nucleation (Vali, 1985). Many laboratory studies as for example Mason and Maybank (1958); Isono et al (1959); Roberts and Hallett (1968); Schaller and Fukuta (1979); Pruppacher and Klett (1997); DeMott (2002); Zuberi et al (2002); Archuleta et al (2005); Mangold et al (2005); Kanji and Abbatt (2006); Knopf and Koop (2006); Möhler et al (2006); Marcolli et al (2007); Eastwood et al (2008); Welti et al (2009); Kulkarni and Dobbie (2010) have shown that mineral dust is a good ice nucleus (IN) in both immersion and deposition nucleation mode and usually initiate nucleation at rather high temperatures and low relative humidities. This statement is supported by field studies (DeMott et al, 2003b;Richardson et al, 2007;Klein et al, 2010) where high concentrations of mineral dust led to a significant increase in the ice crystal number concentration.…”
Section: Introductionmentioning
confidence: 99%